Écouter la voix des esclaves avec Médéric-Louis-Élie Moreau de Saint-Méry et Jean-Jacques Rousseau - Olivier-Serge Candau (Études Caribéennes)
Listening to the voices of slaves with Médéric Louis-Élie Moreau de Saint-Méry and Jean-Jacques Rousseau. Moreau de Saint-Méry was in favour of a fully Creole society, and in his Description … of life on Saint-Domingue in the eighteenth century he reflects on the ties which are woven between individuals, united by their common history, and rapidly developing language practices. We are therefore proposing a re-reading of Moreau de Saint-Méry’s historical and cultural chronicle, which is at the intersection of a reflection on the articulation between society, parlance and languages. This is driven by the Essai sur l’origine des langues, notably in chapters 8–11 which are devoted to the distinction between the languages of the North and South. The thinking of Rousseau provides an operational framework, in both methodological et epistemological terms, for a better understanding of Moreau de Saint-Méry’s approach in recognising a developing Creole parlance emerging from a flourishing society. By dramatising the word and setting the stage for the behaviour of Creole slaves, Moreau de Saint-Méry transforms the simple house into a vast auditorium in which the use of language takes centre stage. In recognising black Creoles as actors in this new setting of Saint-Domingue, the author blurs the relationships between the colony and the slaves and renders the reader’s focus on race at least insufficient, if not ineffective.